Rendimiento de la Tercera Soca de Arroz (Oryza Sativa l.), variedad Capirona con diferentes niveles de fertilización en el valle del Bajo Mayo - San Martín - Chávez Oliveira, Otto (2006)
Rice (Oryza sativa L.} is one of the main crops in San Martin with over 90 000 hectares by 2014 and a production bordering the 500 000 tonnes of paddy rice, making the region the second producing area in nationally, contributes 17% of national production and occupies 40% of the economically active in rural areas population (FUDES, 2003). in the low May from the year 2000 approximately, farmers are managing regrowth rice variety Capirona, obtaining variable yields from 4 000 - 5 000 kg I Ha. At the end of the year 2,004 this research in the Cacatachi District was conducted, managing the third outbreak of rice with different levels of fertilization, taking as precedent the work done by GARCIA (2,003), LOPEZ (2,003 } and URKU Amazonian Studies (2,004), who conduct research in the valley of Bajo Mayo are implementing a package of management for the first and second rice crop regrowth. This paper therefore justified in the sense that the feasibility of managing soca rice variety Capirona, can be taken into account by farmers that have certain level of knowledge especially in the dose of fertilizer to use and control -malezas, two of the main cultural practices considered the bottleneck in handling soca.